Helping Relationships From Significant Others Scale: Chinese Version. (November 2022) - Chao, Shu-Mei; Yen, Miaofen; Teng, Hsiu-Lan; Natashia, Dhea; Yueh, Fang-Ru
Using the helping relationships from significant others (HRSO) scale assists patients, such as those with chronic kidney disease (CKD), in adopting a healthy lifestyle to decelerate disease progression, complications, and mortality. To study the efficacy of the scale, we recruited a convenience sample ( n = 250) of patients with CKD from a nephrology clinic in southern Taiwan. Principal axis factor analysis and a promax rotation revealed a 15-item, three-factor explanation of 68.44 % of the total variance. The confirmatory factor analysis showed a good fit. The Composite reliability was .91, .89, and .92 in the same factors. Cronbach's alpha was .90 for the 15-item scale, with the 3 subscales ranging from .86 to .91. The split reliability was .73. The HRSO is a valid and reliable scale to measure significant others' support of patients with CKD in maintaining a healthy lifestyle.